PERAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI TERHADAP HUBUNGAN FRAUD DIAMOND DAN PENDETEKSIAN FINANCIAL STATEMENT FRAUD (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - Meliana Sugita; Edfan Darlis; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study is to determine the role of the audit committee in moderating the fraud diamond relationship to the detection of financial statements fraud. This research uses financial targets, ineffective monitoring, change in auditors and change in director in perspective of fraud diamond as independent variable. Dependent variable in this research is financial statement fraud and audit committee as moderation variable. Samples used in this study are 91 manufactured companies that listed in Indonesia Stock Exchange during the period 2014-2016. The types of data used are secondary data, in the form of annual reports of companies listed on the IDX during the period 2014-2016. The sample is determined by using purposive sampling method. Analysis of data is carried out using moderate regression analysis with the aid of SPSS version 21 computer program.The result of hypothesis testing showed that audit committee is able to moderate the relationship of financial targets and ineffective monitoring toward financial statement fraud. However, the audit committee is not able to moderate the relationship of change in auditor and the change in director toward financial statement fraud.Keywords: Financial Statement Fraud, Financial Targets, Ineffective Monitoring, Change in Auditor, Change in Director,and Audit Committee.